Potential Prophylactic Treatments for COVID-19 - Noam Ben-Zuk; Ido-David Dechtman; Itai Henn; Libby Weiss; Amichay Afriat; Esther Krasner; Yoav Gal (Viruses, 2021)
The World Health Organization declared the SARS-CoV-2 outbreak a Public Health Emergency of International Concern at the end of January 2020 and a pandemic two months later. The virus primarily spreads between humans via respiratory droplets, and is the causative agent of Coronavirus Disease 2019 (COVID-19), which can vary in severity, from asymptomatic or mild disease (the vast majority of the cases) to respiratory failure, multi-organ failure, and death. Recently, several vaccines were approved for emergency use against SARS-CoV-2. However, their worldwide availability is acutely limited, and therefore, SARS-CoV-2 is still expected to cause significant morbidity and mortality in the upcoming year. Hence, additional countermeasures are needed, particularly pharmaceutical drugs that are widely accessible, safe, scalable, and affordable. In this comprehensive review, we target the prophylactic arena, focusing on small-molecule candidates. In order to consolidate a potential list of such medications, which were categorized as either antivirals, repurposed drugs, or miscellaneous, a thorough screening for relevant clinical trials was conducted. A brief molecular and/or clinical background is provided for each potential drug, rationalizing its prophylactic use as an antiviral or inflammatory modulator. Drug safety profiles are discussed, and current medical indications and research status regarding their relevance to COVID-19 are shortly reviewed. In the near future, a significant body of information regarding the effectiveness of drugs being clinically studied for COVID-19 is expected to accumulate, in addition to information regarding the efficacy of prophylactic treatments.